Respuesta :
[tex]x,\ x+2,\ x+4-\text{three consecutive even integers}\\\\\text{The equation:}\\\\x+(x+2)+(x+4)=36\\\\3x+6=36\ \ \ \ |-6\\\\3x=30\ \ \ \ |:3\\\\x=10\\x+2=12\\x+4=14[/tex]
Answer:
X + X + 2 + X + 4 = 30
Step-by-step explanation:
Here, X represent the first integer,
If the other 2 integers are succeeding even integers,
Then second integer = X + 2,
Third integer = X + 4
Thus, the sum of these integers = X + X + 2 + X + 4
According to the question,
Sum of these integers = 36
X + X + 2 + X + 4 = 30
Which is the required equation that is used to find the first integer.